Anthropometric profiles and physical characteristics in competitive female english premiership rugby union players - Yao, X.; Curtis, C.; Turner, A.; Bishop, C.; Austerberry, A.; Chavda, S. (International Journal of Sports Physiology and Performance, 2021)
Rugby union (RU) is a field-based team sport with a large number of high-intensity actions such as sprinting, change of direction, tackling, scrummaging, rucking, and mauling. Competitive success in female RU has previously been related to anthropometric and physical characteristics, and with the recent introduction of professionalism in female rugby, characterizing such physical attributes may provide insight into selection and training processes.